Still Me : Me Before You #3 - Moyes, Jojo, 1969- (New York : Pamela Dorman Books/Viking, 2018)
Louisa Clark arrives in New York to start a new life and a long-distance relationship with Ambulance Sam while working for the super-wealthy Gopniks, a job that introduces her to New York high society and a secretive man who reminds her of her own past.
Keywords: Young women -- Fiction; English -- United States -- Fiction; Man-woman relationships -- Fiction; Young women -- Fiction; English -- United States -- Fiction; Man-woman relationship -- Fiction; Romance fiction